Comparison of modeled lactate threshold 2 with maximal lactate steady state in running and cycling - Keller, Sebastian; Fischer, Jonas; Ji, Sanghyeon; Zwingmann, Lukas; Wahl, Patrick (International Journal of Sports Medicine, 2025)
This study investigated (1) the agreement of modeled lactate threshold 2 using peak oxygen uptake, cost of locomotion, and fractional utilization of peak oxygen uptake at lactate threshold 2 with the maximal lactate steady state in running and cycling; (2) the impact of different cost of locomotion determination methods on the accuracy of the model and (3) the contributions of peak oxygen uptake, cost of locomotion, and fractional utilization of peak oxygen uptake at lactate threshold 2 to the work rate at maximal lactate steady state. Thirty-four endurance-trained athletes (27.7±6.9 y, 56.2±5.5 ml∙kg−1∙min−1) completed an incremental step test on a treadmill or a cycling ergometer. Peak oxygen uptake, cost of locomotion at lactate threshold 1, at 80% of peak oxygen uptake, and at lactate threshold 2, and fractional utilization of peak oxygen uptake at lactate threshold 2 were assessed. Two to five 30-minute constant work rate tests were performed for maximal lactate steady state determination. Moderate to good agreement was found between modeled work rate corresponding to lactate threshold 2 and the maximal lactate steady state for running and cycling (intraclass correlation coefficient≥0.698) with the smallest mean difference (±limits of agreement) for cost of locomotion determined at lactate threshold 2 with −2.0±5.2 and −0.9±6.0%, respectively. Overall, 83 and 79% of the variance in the maximal lactate steady state was explained by peak oxygen uptake, cost of locomotion determined at lactate threshold 2, and fractional utilization of peak oxygen uptake at lactate threshold 2, respectively. Peak oxygen uptake and cost of locomotion determined at lactate threshold 2 contributed the most to the regression R2 in running (54 and 40%) and cycling (74 and 51%), while fractional utilization of peak oxygen uptake at lactate threshold 2 had the smallest contribution (4 and 5%). Based on the high accuracy of the model with the major contribution of peak oxygen uptake and cost of locomotion determined at lactate threshold 2, the work rate corresponding to the maximal lactate steady state could be improved focusing on these two variables during training.
Keywords: maximal metabolic steady state; performance diagnostics; performance modeling; aerobic capacity; cost of locomotion; endurance performance